Blood Plasma Minerals and Biochemical Profile of Anestrus and Endometritic Cows Reared in Tribal Areas of Himachal Pradesh, India - Sharma, Ankita; Singh, Madhumeet; Kumar, Pravesh (The Indian Journal of Animal Reproduction, 2022)
Blood samples were collected from 227 infertile (Endometritis; n=123, Anoestrus; n=104) cows from five different tribal locations of Himachal Pradesh viz. Lahaul, Spiti, Kinnaur, Pangi and Bharmour. Significantly, lower levels of potassium were recorded in the Kinnaur district in both anestrus (3.33±0.09mmol/L) and endometritic (3.30±0.12mmol/L) cows as compared to other tribal areas. Significantly, higher levels of AST (p
Keywords: Anestrus; Endometritis; Tribal; Infertility